2015
DOI: 10.4103/0971-9784.159800
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of feasibility and efficacy of Class IV laser therapy for postoperative pain relief in off-pump coronary artery bypass surgery patients: A pilot study

Abstract: Background:Laser therapy, for its established analgesic properties with minimal side effects, has been used for the treatment of chronic pain. However, it has not been used for the treatment of acute postoperative pain. This pilot study was designed to assess the feasibility and efficacy of Class IV laser on postoperative pain relief following off-pump coronary artery bypass graft (OPCABG) surgery, as a component of multimodal analgesia (MMA) technique.Methods:This open observational prospective study comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…9 LLLT is a non-invasive method with approximately no side effects and its cost is more reasonable. Previous studies have documented various mechanisms for the efficacy of laser on pain relief, including photobiomodulation, which caused certain reactions such as increased production of ATP, prostaglandins 34,35 and beta-endorphins, decreased bradykinin levels, inhibition signal transduction from type C fibers, 32 and increased secretion of pain relief neurotransmitters such as serotonin. 36 In addition, LLLT can increases blood circulation, thus increases oxygen available for tissues and the pain-causing factors are diverted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9 LLLT is a non-invasive method with approximately no side effects and its cost is more reasonable. Previous studies have documented various mechanisms for the efficacy of laser on pain relief, including photobiomodulation, which caused certain reactions such as increased production of ATP, prostaglandins 34,35 and beta-endorphins, decreased bradykinin levels, inhibition signal transduction from type C fibers, 32 and increased secretion of pain relief neurotransmitters such as serotonin. 36 In addition, LLLT can increases blood circulation, thus increases oxygen available for tissues and the pain-causing factors are diverted.…”
Section: Discussionmentioning
confidence: 99%
“…The results of 8 other studies that were studied in this review showed that LLLT was effective in reducing postoperative pain in patients with breast augmentation surgery, 26 inguinal hernia surgery, 27 tonsillectomy, 28,31 episiotomies, 29 tibial fracture surgery 24 and coronary artery bypass surgery. 32,33 In addition, the laser can reduce the use of pain relief medication, thus protecting the patient from the complications of these drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 24 ] and Karlekar et al . [ 25 ] and could support the higher influence of affective aspects on the McGill scores when applied to postoperative cardiac patients.…”
Section: Discussionmentioning
confidence: 96%